The Development of the PBL Activities to Enhance the Grade 5 Students’ Thai Language Critical Reading Ability - Khanbut, Thanjira; Rittidetch, Prasopsook; Boontongtueng, Poosit (Journal of Education Rajabhat Maha Sarakham University, 2023)
The objectives of this research were to 1) develop the problem-based learning activities to enhance the students’ critical reading ability in Thai language course as the effectiveness as 80/80 criterion. 2) compare the sample’ critical reading ability, and 3) to study the sample’ satisfaction toward the learning model. The sample consisted of the 41 Mathayomsuksa 5/6 students who studied in second semester, academic year of 2022, Roi-Et Wittayalai School, Roi-Et Province. The sample used the cluster random sampling. The research tools were: 1) the PBL lesson plans 2) a competency test, and 3) a 5 level rating scales satisfaction form. The statistics were percentage, mean, standard deviation, and t-test. The research results were as follows: 1) The PBL efficiency was at 81.92/82.93 as the research criteria 2) the sample’ critical reading ability after learning with the model was higher as the statistical significant as .05. 3) The overall for students satisfied after learning with the model was at the highest level.